Recovery of a dystrophic Red Latosol (Oxisol) and pasture as a function of gypsum in the Cerrado biome - Backes, Clarice; Marques Santos, Alessandro Jose; Rodrigues, Lucas Matheus; Teodoro, Arthur Gabriel; Ribon, Adriana Aparecida; Villas Boas, Roberto Lyra [UNESP]; Pereira, Lorena Marques; Franco, Yago Magalhaes (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2017)
This study was conducted to evaluate the chemical effects of gypsum on the soil and on the recovery of a pasture established with palisade grass (Urochloa brizantha) in a Cerrado biome region. A randomized block experimental design with six treatments and four replications was adopted. Treatments consisted of five levels of gypsum ( 0, 450, 900, 1800, and 3600 kg ha(-1)) plus an unmanaged control treatment (without gypsum or additional chemical fertilizers). The gypsum treatments received addition of fertilizer (200 and 40 kg ha(-1) of N and P respectively). The soil treatment started in October 2012. The application of gypsum provided an increase in plant height, number of tillers, and dry matter of the shoots of palisade grass. Gypsum combined with chemical fertilizers provided an increase in productivity compared with chemical fertilizers alone. The use of gypsum improved the chemical characteristics of the soil, increasing calcium and sulfur in the deeper layers, consequently, providing greater development of the palisade grass root system. High gypsum levels impaired the development of the root system, especially in the 0.20-0.40 m layer. Gypsum provides recovery of soil and degraded pastures.
Keywords: degraded pasture; palisade grass; soil conditioner; Urochloa brizantha